The Influences of Social Media Marketing, Service Quality and EWOM on Purchase Intention - Heidy Maslim; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2021)
The development of internet technology and increasing use of social media have encouraged most industrial sectors to apply this technology to support the progress of a business, including the creative economy sector. The interior design subsector as a part of the creative economy does not escape digitization, from design methods, marketing strategies, to transaction processes especially during the Covid-19 pandemic in 2020 which causes many processes to be done online. This study aims to examine the previous research model, namely the influence of social media marketing activities, service quality, and eWOM on purchase intention mediated by emotional experience. This study focuses on Dekoruma, one of many brands providing interior design products and services in Indonesia. Respondents were obtained by snowball sampling technique with 72 respondents who met the requirements. Data were collected through a questionnaire consisting of 28 questions distributed online and were analysed using the PLS-based SEM method. The results show that social media marketing activities and eWOM have a positive effect on purchase intention, and this influence will be stronger when mediated by emotional experience. However, service quality does not directly affect purchase intention, but must be mediated by emotional experience.